An investigation into attitudes of nurses towards Patients’ aggression in mental Health Hospitals in Sulaimani City \ Kurdistan -Iraq - Abdulkarim, Araz Mohammed (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Patients’ aggression remains a challenging issue for nurses in mental health hospitals. Nurses' attitudes and perceptions toward aggression can be projected into management and level of care. Psychiatric patients require special care and require a positive attitude from nurses to reduce aggressive behaviors. Objective: This study aimed to describe attitudes among nurses towards patients’ aggression. In addition to determine the difference in the attitude in regard to some variables among those nurses. Materials and Methods: Sixty nurses working in the two governmental mental hospitals in Sulaimani city, who met certain criteria were recruited for this cross-sectional study, using a convenience sampling technique. A self-reported questionnaire was developed and consisted of three parts, The sociodemographic characteristics, workplace environment, and the attitude toward aggression scale (ATAS), The scale consists of eight subscales of attitudes. The period of data collection started from January 2023 to May 2023. The collected data were statistically analyzed using SPSS- Version 22. Results: The overall average mean score of attitudes was determined (37.7 ± 3.835) in the acceptable-normal reaction attitude scale, which attributed to a highest mean score, which reflects a positive attitude. Followed by a violent reaction attitude scale (34.1± 3.597) viewing aggression as an assault reaction. In addition, nurses' scientific degrees in nursing education, age, gender, and ward-work unit were variables that significantly affect the differences in attitude (P value < 0.05, 0.01). Conclusions: The findings entail that the nursing staff working in mental health hospitals in Sulaimani holds a positivenegative attitude toward patients’ aggression, which may reflect the patient -centered nursing approach used by them.
Keywords: Nurse; attitude; aggression; patient; ATAS